2006
DOI: 10.1073/pnas.0602048103
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide cross-linked protein represents a significant fraction of ALS-associated Cu, Zn-superoxide dismutase aggregates in spinal cords of model mice

Abstract: Point mutations in Cu, Zn-superoxide dismutase (SOD1) cause a familial form of the neurodegenerative disease amyotrophic lateral sclerosis (ALS). Aggregates of mutant SOD1 proteins are observed in histopathology and are invoked in several proposed mechanisms for motor neuronal death; however, the significant stability and activity of the mature mutant proteins are not readily explained in such models. Recent biochemical studies suggest that it is the immature disulfide-reduced forms of the familial ALS mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
188
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(197 citation statements)
references
References 47 publications
7
188
0
2
Order By: Relevance
“…30-32. More recently, studies from transgenic mouse models of FALS have suggested that the intermolecular disulfide-linked SOD1 aggregates are associated with disease toxicity (8,23). One study used immunoprecipitation to conclude an apparent SOD1 species of Ϸ35 kDa was a complex between SOD1 and Bcl-2 (19), albeit our mass spectrometric analysis offered no support for any linkage to Bcl-2, at least in SALS.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…30-32. More recently, studies from transgenic mouse models of FALS have suggested that the intermolecular disulfide-linked SOD1 aggregates are associated with disease toxicity (8,23). One study used immunoprecipitation to conclude an apparent SOD1 species of Ϸ35 kDa was a complex between SOD1 and Bcl-2 (19), albeit our mass spectrometric analysis offered no support for any linkage to Bcl-2, at least in SALS.…”
Section: Discussionmentioning
confidence: 55%
“…Many studies have investigated the possibility of structural differences in SOD1 caused by mutations as a basis for such toxic effects (4,5). Although several common features of mutant SOD1 proteins such as instability, higher sensitivity to denaturing conditions, and propensity to form aggregates are found to be associated with mutant SOD1-linked FALS disease course and severity (6)(7)(8)(9)(10)(11), no single biochemical feature has been found to be shared by all identified mutant SOD1s, nor has there been a single molecular feature of SOD1 identified to be associated with SALS.…”
Section: Amyotrophic Lateral Sclerosis (Als) Is a Devastating Motor Nmentioning
confidence: 99%
“…In the model that was most closely examined, G93A, these forms appeared to predominate, and were present throughout life. The hSOD1 that is present as insoluble aggregates in terminal spinal cords is partially composed of disulfidelinked dimers and multimers (23,24). Because SOD1 is mainly present in the reducing cytosol, the presence of the oxidized species is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, they accumulate in the final phase concomitantly with the appearance of overt symptoms, and are commonly suggested to cause the disease (24,26). Their appearance probably reflects a terminal disruption of the protein surveillance and degrading systems.…”
Section: Aggregates or Soluble Misfolded Sod1 As Als-inducing Speciesmentioning
confidence: 99%
“…Although the exact cellular sites and mechanisms of toxicity are unknown, aberrant SOD1 protein oligomerization has been strongly implicated in disease causation (7,8). Several recent publications have presented compelling evidence that abnormal disulfide cross-linking of ALS-mutant SOD1 plays a role in this oligomerization, and disulfide-linked SOD1 multimers have been detected in neural tissues of SOD1-ALS transgenic mice that are presumed to be components of higher-molecular-weight species or intermediates in their formation (7,(9)(10)(11).…”
mentioning
confidence: 99%